Detecting cancerous human liver cells with high performances using photonic crystals - Soltani, Osswa; Francoeur, Sebastien; Kanzari, Mounir (Physica. B, Condensed matter, 2023)
We propose a one-dimensional photonic crystal that can be used to probe pathological tissues and identify the presence of human liver cancer cells. The identification of cancerous tissues is achieved with interferometric sensitivity by probing optical changes in refractive index and absorption, which are significant enough to strongly affect the position, intensity, and line width of transmission modes. Using experimentally determined optical properties of healthy and cancerous cells, we optimize the sensitivity and resolution of the device as a function of the physical parameters and incident angle. In contrast to prior work, we fully consider all losses occurring through the optical structure. An optimum transmittance of 90%, a quality factor of 721 and a sensitivity of 1033 nm/RIU are achieved, demonstrating the capacity of this device to detect cancer cells. These results could pave the way for the realization of low-cost sensor with high sensitivity for biomedical diagnostic applications.